Phospholipid translocation captured in a bifunctional membrane protein MprF - Danfeng Song (Nature Portfolio, 2021)
The Multiple Peptide Resistance Factors (MprFs) utilize two separate domains to synthesize and translocate aminoacyl phospholipids to the outer leaflets of bacterial membranes. Here authors present cryo-electron microscopy structures of MprF homodimer from Rhizobium tropici (RtMprF) at two different states in complex with lysyl-phosphatidylglycerol (LysPG).